The efficacy and safety of Jin's three-needle therapy vs. placebo acupuncture on anxiety symptoms in patients with post-stroke anxiety: A study protocol for a randomized controlled trial - Li, Meichen; Wang, Yuting; Li, Keyi; Xu, Xiaoyan; Zhuang, Lixing (Frontiers in Psychiatry, 2022)
Background:A large number of clinical RCTs have verified that Jin's three-needle therapy（JTNT） has a great contribution to promoting the function of paralyzed limbs and relieving anxiety disorders for patients with post-stroke anxiety（PSA）. However, there is still a lack of sham needle control, and its placebo effect cannot be ruled out. This study firstly verifies the real effectiveness of JTNT. Besides, the changes of serum indexes on the hypothalamic-pituitary-adrenal axis（HPA axis) are observed dynamically by Enzyme-Linked ImmunoSorbent Assay( ELISA). The activation of different brain regions by JTNT are recorded using resting functional magnetic resonance imaging(rs-fMRI). Therefore, we can provide more practical and powerful evidence-based medical evidence for clinical decisions. Method: This is a 16-week parallel, single-blind, random, controlled trial, including baseline, 4 weeks of treatment, and 12 weeks of follow-up. A total of 76 participants will be randomly divided into two groups in the proportion of 1: 1. Patients will receive Jin's three-needle therapy in the experimental group and accept sham needle treatment in the control group. Outcomes cover three types of indicators, including scale indicators, serum indicators, and imaging indicators. The primary outcome is the change in the performance of anxiety symptoms, which is estimated by the 14-item Hamilton Anxiety Rating Scale (HAMA-14) and the 7-item Generalized Anxiety Disorder scale (GAD-7). Secondary outcomes are the physical recovery and daily quality of life, which is evaluated by the National Institute of Health stroke scale (NIHSS) and the Modified Barthel Index Score (MBI Scale). Therefore, the assessment of the scale is carried out at baseline, 2nd, 4th, 8, 12, and 16 weeks. Adrenocorticotropin and cortisol will be quantitatively detected by ELISA at baseline and 4 weeks of treatment. In addition, regional homogeneity analysis (ReHo) will be used to record the brain regions activity at baseline and 4 weeks after intervention. Discussion: The study aims to provide high-quality clinical evidence on the effectiveness and safety of JTNT for patients with PSA. In addition, this trial explores a possible mechanism of JTNT for patients with PSA. Clinical Trial Registration: Chinese Clinical Trial Registry, identifier: ChiCTR2200058992.